(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article covers experimental study of knives with different sharpening angles to determine the strength properties of molded half-finished product and associated energy consumption for cutting. Determination of the values of the limiting shear stress of products depending on moisture content of the dough and the radius of rounding of the knife.